DETERMINANTS OF COMMUNITY FINANCIAL STATEMENT QUALITY: TANAH LAUT DISTRICT A VILLAGE FINANCIAL SYSTEM AND HUMAN RESOURCE COMPETENCE - Yuli Fitriyani; Maulida Hirdianti Bandi; Noor Amelia (Jurnal Kompetitif, 2023)
The quality of village financial reports is supported by several factors such as the implementation of the village financial system and competency of human resources. This research aims to determine the influence of the village financial system and human resource competency on the quality of village financial reports in three sub-districts of Tanah Laut Regency. This research is research with a quantitative approach. The research results show that the village financial system partially has a significant effect on the quality of village financial reports. Human resource competency partially has a significant effect on the quality of village financial reports. The quality of Village Financial Reports is influenced by qualified human resources and an optimal Siskeudes system. HR competency can be interpreted as the suitability of educational background and responsibilities as village treasurer. It is felt that Siskeudes will make it easier to complete village financial reporting.